Homozygous GRHPR C.494G>A mutation is deleterious that causes early onset of nephrolithiasis in West Bengal, India - Chatterjee, Arindam; Sarkar, Kunal; Bank, Sarbashri; Ghosh, Sudakshina; Kumar Pal, Dilip; Saraf, Siddharth; Wakle, Dhansagar; Roy, Bidyut; Chakraborty, Santanu; Bankura, Biswabandhu; Chattopadhyay, Debprasad; Das, Madhusudan (Frontiers in Molecular Biosciences, 2022)
Pediatric nephrolithiasis (NL) or Kidney stone disease (KSD) is an untethered topic in Asian population. In Western countries, the annual incidence of paediatric NL is around 6- 10%. Here, we present data from West Bengal, India, on lower age (LA, 0-20 years) NL and its prevalence for the first time. To discover the mutations associated with KSD, twenty-four (18+6) rare LA-NL patients were selected for Whole Exome Sequencing (WES) and Sanger sequencing, respectively. It was found that GRHPR c. 494G>A mutation (MZ826703) is predominant in our study cohort. This specific homozygous mutation is functionally studied for the first time directly from human peripheral mononuclear cell (PBMC) samples. Using expression study with biochemical activity and computational analysis we assumed that the mutation is pathogenic with loss of function. Moreover, three genes, AGXT, HOGA1 and GRHPR with Novel variants known to cause hyperoxaluria were found frequently in the study cohort. Our study analyses the genes and variations that cause LA-NL, as well as the molecular function of the GRHPR mutation, which may serve as a clinical marker in the population of West Bengal, Eastern India.